2019
DOI: 10.1002/tox.22876
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of a naturally occurring sapogenin diosgenin on underlying mechanisms of Ca2+ movement and cytotoxicity in human prostate cancer cells

Abstract: Literature has shown that diosgenin, a naturally occurring sapogenin, inducedcytotoxic effects in many cancer models. This study investigated the effect of diosgenin on intracellular Ca 2+ concentration ([Ca 2+ ]i) and cytotoxicity in PC3 human prostate cancer cells. Diosgenin (250-1000 μM) caused [Ca 2+ ]i rises which was reduced by Ca 2+ removal. Treatment with thapsigargin eliminated diosgenin-induced [Ca 2+ ]i increases. In contrast, incubation with diosgeninabolished thapsigargin-caused [Ca 2+ ]i increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 50 publications
0
12
0
1
Order By: Relevance
“…For patients who have undergone radical surgeries or completed radiotherapy and chemotherapy, TCM treatment can also improve the body's immunity and inhibit tumor recurrence and metastasis. Recent studies have shown that the anticancer and cancer inhibitory theory of TCM mainly include antiangiogenesis, tumor cell proapoptosis, cytotoxicity, extracellular matrix antidegradation, improvement of body immunity, participation in regulation of cell signal transduction, and the attenuation and synergistic effect of radiotherapy and chemotherapy [ 24 , 25 ]. Chongqing Traditional Chinese Medicine Hospital is a special hospital of TCM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients who have undergone radical surgeries or completed radiotherapy and chemotherapy, TCM treatment can also improve the body's immunity and inhibit tumor recurrence and metastasis. Recent studies have shown that the anticancer and cancer inhibitory theory of TCM mainly include antiangiogenesis, tumor cell proapoptosis, cytotoxicity, extracellular matrix antidegradation, improvement of body immunity, participation in regulation of cell signal transduction, and the attenuation and synergistic effect of radiotherapy and chemotherapy [ 24 , 25 ]. Chongqing Traditional Chinese Medicine Hospital is a special hospital of TCM.…”
Section: Discussionmentioning
confidence: 99%
“…Diosgenin increases the phosphorylation level of JNK to inhibit the proliferation of the breast cancer cells with a high expression of human epidermal growth factor receptor and to promote cell apoptosis, possibly by inhibiting Akt and mTOR phosphorylation [ 35 ]. Diosgenin inhibits the proliferation, migration, and invasion of PCa cell PC-3 in by suppressing the expression of VEGF and reducing the activity of matrix metalloproteinases [ 25 , 36 ]. In human chronic myelogenous leukemia K562 cells and HEL cell apoptosis studies, it has been found that G0/G1 cells are more prone to apoptosis, and diosgenin can increase the expressions of thromboxane synthase (TxS) and cyclooxygenase-2 and induce HEL cell differentiation [ 37 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diosgenin can promote NEDD4 E3 ubiquitin protein ligase Ca 2+ levels and flux. Furthermore, this compound causes Ca 2+ -independent cell death in prostate cancer cells [ 329 ]. Diosgenin administration significantly reduces proliferation and viability of prostate cancer cells via inducing autophagy.…”
Section: Autophagy and Prostate Cancermentioning
confidence: 99%
“…Diosgenin was demonstrated to inhibit tumor growth in both MDA-231 and MCF-7 ×enografts in vivo by inhibiting Akt, the Raf/MEK signaling pathway and NF-κB activity to induce apoptosis ( 40 , 52 , 53 ). Therefore, diosgenin may be a potential option for the treatment of cancer ( 27 , 29 , 34 , 35 , 37 , 39 ).…”
Section: Antitumor Effects and Mechanisms Of Diosgeninmentioning
confidence: 99%